Seeds of Conflict and Religious Intolerance in Papua: A Preliminary Study on Tolikara Incident 2015 - Ridwan Ridwan (Review of Islam in Southeast Asia, 2018)
To date, Islam and Christians have built up religious tolerance in Papua. However, nowadays Papua faces the growing of religious intolerance and seeds of conflict. One of its striking cases was Tolikara Incident in 2015. Principally, the incident had destroyed image of the legacy of religious tolerance in Papua. By examining the case comprehensively, this writing explored the context and the complexities of the Incidents. This writing offers a broader perspective to examine the phenomenon of religious intolerance in Tolikara, Papua, by providing a brief conceptual study, as well as reports of several investigation teams. Afterwards, it will describe the profile of Tolikara, GIDI and Muslim in Tolikara as a background to understanding the case holistically. Then, the author will describe the chronology of the event  followed by providing a diagnosis of the seeds of religious intolerance leading to the conclusion and recommendations.